EFEKTIVITAS PEMBENTUKAN ASEAN INSTITUTE FOR PEACE AND RECONCILIATION DALAM MENANGANI KONFLIK DI KAWASAN ASIA TENGGARA - Novriest Umbu Walangara Nau; Jet Sahertian (Andalas Institute of International Studies, 2021)
Various conflicts that occurred in the Southeast Asian region made ASEAN respond quickly. This is realized through the establishment of the ASEAN Institute for Peace and Reconciliation which carries out several functions including research, capacity building, development in expertise, networking, gathering experiences and ASEAN best practices on peace, conflict management and conflict resolution, and post-conflict peace building. However, until now there are still various conflicts that occur. Therefore, this study aims to present the results of an analysis of organizational reporting. To gain a more comprehensive understanding, the researcher uses the theory of Regime Effectiveness and the concept of international regimes. In addition, this study uses a qualitative method with a qualitative descriptive type. This study finds that the organization is not effective in dealing with conflicts in Southeast Asia because the organization is not empowered in conflict resolution efforts, in addition to the application of the ASEAN Way principle and the lack of support from member countries.